Sexual and vertical transmission of visceral leishmaniasis - Andreia P Turchetti; Tayse D Souza; Tatiane A Paixão; Renato L. Santos (Journal of Infection in Developing Countries)
Visceral leishmaniasis (VL) is an important zoonosis caused by Leishmania infantum, which has in the domestic dog its principal vertebrate host. VL is usually transmitted by phlebotomine sand flies, however atypical routes of transmission have been described. In this review we discuss the the role of sexual and vertical transmissions, and their role in the maintenance of VL in canine populations.